Reasons for the Compulsory Nature of the Ukrainians’ Repatriation, from the Western Zones of Occupation to the USSR, after the Second World War (1945 – 1951) - Lyudmyla Strilchuk (Codrul Cosminului, 2016)
During the years of the Second World War millions of people suffered from the compulsory shifts due to the military actions or captivity or due to the remove to the compulsory labour. Ukrainians made an essential part of those who were removed. At the final stage of the Second World War and during the first years after its end all the Ukrainian which appeared on the territory of the soviet zone of occupation were obligatorily repatriated to the USSR. The political fight started when the soviet citizens from the Western Allies’ zones of occupation did not wish to return to the “Soviet Motherhood”. Ukrainian political refugees did not have enough reasons to return to the USSR: fear of punishment by the system for the stay in the captivity or at the compulsory work, non-acceptance of the soviet totalitarian system, protest against repressions, national vexations and pursuit which were specific to the pre-war years. The Soviet regime tried all possible ways to return its citizens to the USSR, and by this not to allow political fleeing from the country. The repatriated citizens became subject to compulsory work with the guilt of staying in the enemy territory.